The interactive ecology of construal in gesture: a microethnographic analysis of peer learning at an EMI university in China - Stevens, Michael P. (2021)
Depictive manual gestures do not appear in isolation, but are motivated by a complex of experiential knowledge, communicative goals, and contextual-environmental factors (Harrison 2018; Kendon 2004; Müller 2014; Streeck 1993, 1994, 2009b). However, little is known about the incremental, moment-by-moment formulation of depictions in elaborate sequences of talk. Furthermore, questions endure about depiction as a learning resource within the contingent interactivity of the foreign language academic classroom. This study explores these questions in the context of subject-related student talk at a Sino-foreign university in China by focusing on how gesturers build expositions through intercorporeal and intersubjective sense making (cf. Merleau-Ponty 1945/2012). Drawing on empirical material from the corpus of Chinese Academic Written and Spoken English (CAWSE), I aim to contribute greater understanding of the intersubjective ecology of depictive gesturing. The study builds on previous research on depictive gestures in the classroom (e.g. Rosborough 2014; Roth & Lawless 2002) by focusing on sequences of gesturing within two distinct classroom tasks: i) dialogic explanations of complex systems and ii) interactional multi-party group discussions. By converging theories of intersubjectivity drawing on Cognitive Grammar (e.g. Langacker 2008; Blomberg & Zlatev 2014) and Conversation Analysis (Heritage & Atkinson 1984; Schegloff 1992), I use microethnography for the investigation of gesture as a cognitive practice (Streeck 2009b; cf. Erickson 1995; Streeck & Mehus 2005). The analysis engages concepts in phenomenology, ecological cognition and enactivism in order to illustrate the publicly displayable achievement of enactive construal in spoken exposition. These analyses expose the ways that speakers depict for intersubjective visualization of the topic-at-hand, and anticipate and react to affordances that occur within the landscape of interaction. Speakers design their depictions, by manipulating construal dimensions in three ways: i) depictions are integrated into the exposition for projecting and delimiting epistemic arenas where construal relations are tailored for specific structural aspects of the depictions, ii) depictions invite participatory frameworks for co-analysis of the topic-at-hand, and iii) speakers refashion their depictions to anticipate previous trouble. Furthermore, the analysis of the interactional order of the tasks illustrates the intercorporeality, the pre-reflective disposition towards sense-making, of construal in the moment-by-moment construction of academic classroom talk. This study has implications that problematize the notion of the body as a communicative resource by obscuring the notions of planning and strategy. Overall, the analysis shows that explanations and discussions involve finely grained attenuation of the corporeal dimensions of spoken language.